Analisis Manajemen Pembelajaran Aktif Berbasis Karakter pada SMP Rintisan Kurikulum 2013 Mandiri di Kecamatan Beji Kota Depok - Susan Febriantina (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
This research is a descriptive research to get factual data about the planning, implementation and supervision of character-based active learning at independent curriculum 2013 junior high schoolsin Depok. It also explores the obstacles to find solutions to solve the problem. Data source in this study includessome junior high schools in Beji sub-district of Depok City which has been given decreed by Balitbang Kemendikbud as independent curriculum 2013 junior high school. Data collection techniques and procedures are used using several sources of evidence; questionnaires, in-depth interviews, documentation studies and archives. Data analysis in this study uses descriptive statistical data analysis techniques by calculating the percentage and provide a review or interpretation of the data obtained so that becomes more clear and meaningful than just the numbers. Character-based active learning planning at independent curriculum 2013 junior high schools in Depok is implemented by developing character values on syllabus and lesson plan and taking into account the principle of the preparation of character-based learning planning. Implementation of character-based active learning in independent curriculum 2013 junior high school in Depok is done by using model, method, learning media, and learning resource according to the characteristics of learners through approach and strengthening of character values. While the supervision of character-based active learning is carried out by the school principal and supervisor/supervisor of the local education office which includes planning supervision, implementation and character-based learning assessment.